Determinant Risks of Adolescent Sex Behavior in Terjun Village - Dhani Syahputra Bukit; Kintoko Rochadi; Alam Bakti Keloko (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Adolescent sexual behavior is a complex issue that has a major impact on the health and well-being of young people worldwide. In today's internet era, it is shaped by many factors, including peer influence, family support, access to pornography, and reproductive health services. This study set out to examine the variables that influence adolescent sexual behavior. Using a cross-sectional design, researchers surveyed 170 adolescents in Terjun Village, selected through random sampling. Data were analyzed with the chi-square test to identify relationships between variables. The results showed that knowledge (p = 0.006), family support (p = 0.0005), and access to pornographic content (p = 0.0005) were significantly related to adolescent sexual behavior. In contrast, reproductive health services (p = 0.196) and peer influence (p = 0.440) did not show a significant relationship. These findings suggest that to help adolescents live healthier and more responsible sexual lives, efforts should focus on comprehensive sex education, strong family support, reproductive health promotion, and policy advocacy that reinforce these strategies Keywords: Adolescent, Sexual Behavior, Health, Risk